Valoración de parámetros físicos, químicos en la maduración artificial de papaya (Carica papaya l.) variedad hawaiana usando acetiluro de calcio cac2 como agente de maduración - Aspiazu Sánchez, Liz Geanella (2021)
The objective of this research was to evaluate the physical and chemical parameters in the artificial ripening of papaya (Carica papaya L.) Hawaiian variety using calcium acetylide CaC2 as ripening agent. A completely randomized design with AxB bifactorial arrangement was applied to determine differences using Tukey's multiple range test at 5% probability, physicochemical variables (texture, pH, brix, acidity) and bromatological variables (humidity, ash, protein, fiber, energy, energy, protein, protein, fiber and acidity) were analyzed, The results of the physicochemical analysis showed that there were significant differences in the texture variable, the best response was the T6 treatment with (1.80 kg/f), the pH with the treatment T1 (5,76), T4 (5,42), T6 (5,54), brix with treatments T4 and T6 with (10.07) and (12.40%), acidity with treatment T6 with the lowest value with (0.8%), at moisture level the best treatment was T6 with (92.22%), ash the T1 with the lowest value (3.20%), protein the treatments T5 and T6 with (4,34) and (5.34%), fiber showed a slight decrease being the best treatment T6 with 1.42%, energy with T6 (0.87kcal), these values recorded in this study are comparable to other similar researches, adjusting to the established parameters. Key words: fruit climacteric, acetylene, bromatological, ethylene